Virginia 4-3-30: seleccion y evaluacion de una nueva linea de tabaco para la zona productora de Santander (Colombia) - Coronado, R.A.=700 1 Moreno, P.A.
(Es, En)
Ilus., 14 ref.
Keywords: NICOTIANA; FITOMEJORAMIENTO; LINEAS PURAS; HIBRIDACION INTERGENERICA; COLOMBIA; TABACO VIRGINIA; HIBRIDACION INTERVARIETAL; REVISTA CORPOICA